2006
DOI: 10.1002/bmc.577
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous liquid chromatographic assay of amantadine and its four related compounds in phosphate-buffered saline using 4-fluoro-7-nitro-2,1,3-benzoxadiazole as a fluorescent derivatization reagent

Abstract: Simultaneous HPLC assay of 1-adamantanamine hydrochloride (amantadine) and its four related compounds [2-adamantanamine hydrochloride (2-ADA), 1-adamantanmethylamine (ADAMA), 1-(1-adamantyl)ethylamine hydrochloride (rimantadine) and 3,5-dimethyl-1-adamantanamine hydrochloride (memantine)] in phosphate-buffered saline (pH 7.4) after pre-column derivatization with 4-fluoro-7-nitro-2,1,3-benzoxadiazole (NBD-F) was developed. Phosphate-buffered saline samples were mixed with borate buffer and NBD-F solution in ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Most HPLC methods involved dansyl chloride [4], o-phthalaldehyde (OPA) [10,11], 4-fluoro-7-nitro-2,1,3-benzoxadiazole (NBD-F) [12] and 1-fluoro-2,4-dinitrobenzene (DNFB) [21] as derivatization reagents to react with tricyclic amines. In this study, dansyl chloride, 4-fluoro-7-nitro-2,1,3-benzoxadiazole and 1-fluoro-2,4-dinitrobenzene were tested to react with memantine hydrochloride and we found that FMOC-Cl derivates of memantine hydrochloride had advantages of higher sensitivity, less interference, and simpler reaction conditions than others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most HPLC methods involved dansyl chloride [4], o-phthalaldehyde (OPA) [10,11], 4-fluoro-7-nitro-2,1,3-benzoxadiazole (NBD-F) [12] and 1-fluoro-2,4-dinitrobenzene (DNFB) [21] as derivatization reagents to react with tricyclic amines. In this study, dansyl chloride, 4-fluoro-7-nitro-2,1,3-benzoxadiazole and 1-fluoro-2,4-dinitrobenzene were tested to react with memantine hydrochloride and we found that FMOC-Cl derivates of memantine hydrochloride had advantages of higher sensitivity, less interference, and simpler reaction conditions than others.…”
Section: Discussionmentioning
confidence: 99%
“…1) for UV or fluorimetric detection. The assay of tricyclic amines is always performed using precolumn [4,[10][11][12] derivatization methods, or other detections, MS [13,14]. And memantine hydrochloride also has been determined by GC-MS [15] and UPLC [16].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-phase extraction (SPE) is a simple, efficient, and solvent-reducing alternative that has been successfully used to analyze various chemical residues in honey samples. [21][22][23] In light of the procedures for derivatization of AMA with NBD-F of Higashi et al(2006), 16 we made a slight modification by dissolving the sample in borate buffed and with fluorescence detection at an excitation wavelength of 470 nm and an emission wavelength of 530 nm. When these conditions were applied in our research, the longest retention times of the AMA and IS derivatives were obtained with 16.9 min and 30.2 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Briefly, each 400 µL solution for the calibration or extracted sample solution was transferred to an HPLC brown glass vial, and then 100 µL NBD-F solution (21.8 mmol/L in acetonitrile, stored at -20 ℃, restored to room temperature before use) was added in. The mixture was allowed to react for 12 min at 60 ℃ and then placed on ice to stop the derivatization reaction.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation